Meningkatkan Gairah Belajar Bulutangkis Melalui Model Pendekatan Taktis pada Siswa Kelas X di SMA Negeri 2 Subang - Fazka Affarizqa Mulyana; Carsiwan; Riansyah (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This classroom action research aimed to describe the implementation of a tactical approach to improve the learning enthusiasm of Grade X students in badminton instruction at SMAN 2 Subang. The participants were 43 students. The intervention included a pre-cycle, Cycle I, and Cycle II through planning, action, observation, reflection, and follow-up stages. Data were collected using an observation sheet with seven indicators: attention, activeness, perseverance, resilience, participation, game involvement, and tactical application. Quantitative descriptive analysis used mean scores, percentages, categories, and frequency distributions. The results increased from 42.77% in the pre-cycle to 69.85% in Cycle I and 88.12% in Cycle II. All students were in the low and very low categories in the pre-cycle; 88.37% reached the good category in Cycle I; and 90.70% reached the very good category in Cycle II. The tactical approach improved game involvement, willingness to discuss, persistence in correcting errors, and tactical application. It can therefore be used as an alternative model for badminton instruction in physical education. Keywords: Badminton, Learning Enthusiasm, Tactical Approach, Classroom Action Research, Physical Education